(untitled) (Research, Society and Development, 2022)
Introduction: Currently there is a growing trend for the installation of implants immediately after tooth extraction, since respecting the principles for the use of said technique, it has been shown to reduce treatment time and reduce morbidity, as it eliminates a surgical step. Objective: To report a series of clinical cases of immediate implant placement in the anterior maxillary region, with provisionalization, bone graft with biomaterial, and tissue compensation through connective tissue graft. Methods: After immediate installation of the implants in fresh alveoli, tissue compensation was performed using bone graft and connective tissue. Temporary crowns were installed on the implants due to the excellent torque obtained in their installation. After five months, the permanent ceramic prostheses were installed. Conclusion: Immediate implants with immediate temporization present satisfactory results in the anterior region with the use of bone biomaterial and connective tissue graft.